Do they Order this Better in France? Eliot and Theory - Brlek, Tomislav (2011)
Assessing the theoretical underpinning of Eliot's work and the impact of the French intellectual tradition on it, the paper analyzes the neglect of this aspect of his work in the Anglophone reception.